The effects of altered DNA damage repair genes on mutational processes and immune cell infiltration in esophageal squamous cell carcinoma - Huangbo Yuan; Tao Qing; Sibo Zhu; Xiaorong Yang; Weicheng Wu; Kelin Xu; Hui Chen; Yanfeng Jiang; Chengkai Zhu; Ziyu Yuan; Tiejun Zhang; Li Jin; et al. (Cancer Medicine, 2023)
Abstract Background Defects in DNA damage repair (DDR) pathways lead to genomic instability and oncogenesis. DDR deficiency is prevalent in esophageal squamous cell carcinoma (ESCC), but the effects of DDR alterations on mutational processes and tumor immune microenvironment in ECSS remain unclear. Methods Whole‐exome and transcriptome sequencing data of 45 ESCC samples from Taizhou, China, were used to identify genomic variations, gene expression modulation in DDR pathways, and the abundance of tumor‐infiltrating immune cells. Ninety‐six ESCC cases from The Cancer Genome Atlas (TCGA) project were used for validation. Results A total of 57.8% (26/45) of the cases in the Taizhou data and 70.8% (68/96) of the cases in the TCGA data carried at least one functional impact DDR mutation. Mutations in the DDR pathways were associated with a high tumor mutation burden. Several DDR deficiency‐related mutational signatures were discovered and were associated with immune cell infiltration, including T cells, monocytes, dendritic cells, and mast cells. The expression levels of two DDR genes, HFM1 and NEIL1, were downregulated in ESCC tumor tissues and had an independent effect on the infiltration of mast cells. In the Taizhou data, increased expression of HFM1 was associated with a poor prognosis, and the increased expression of NEIL1 was associated with a good outcome, but no reproducible correlation was observed in the TCGA data. Conclusion This research demonstrated that DDR alterations could impact mutational processes and immune cell infiltration in ESCC. The suppression of HFM1 and NEIL1 could play a crucial role in ESCC progression and may also serve as prognostic markers.